Knights of the Holy Land : the Crusader Kingdom of Jerusalem - Rozenberg, Silvia, (The Israel Museum, 1999)
The crusading movement bequeathed to its future historians a legacy of sources unrivalled in their range and variety. 'Crusade Texts in Translation' presents these sources in detail as well as the motivations and viewpoints, military efforts and spiritual lives, of the participants in the crusades.